The Quality of Arguments Made by EFL University Students in Their Conceptual Papers (RETAIN, 2020)
Argumentative writing is often described as a highly complex task that places enormous difficulty for EFL students. It is a genre of writing where students demonstrate their critical thinking as they express opinions with detailed supporting evidence. Some previous studies revealed that Indonesia EFL university students are unable to develop well-constructed arguments. To build a sound argument, students are expected to consider the elements of argument and the quality of reasoning. Limited number of research that assessed the quality of argument failed to value the presence these aspects. Therefore, the purpose of this study is to describe the quality of arguments in EFL university students’ conceptual papers, by assessing on both aspects of argumentation. Qualitative content analysis is employed to answer the research questions. The findings show that most arguments are unsound with irrelevant, not acceptable, and weak supports. Most university EFL students participating in this study also failed to include all six elements of argumentation. However, in terms of the surface structure, the majority of arguments are in a well-organized manner.